SOMATOFORM AUTONOMIC DYSFUNCTION IN PATIENTS WITH IRRITABLE BOWEL SYNDROME: A SYSTEMATIC REVIEW OF DIAGNOSTIC BIOMARKERS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Somatoform autonomic dysfunction (SAD) represents a complex neuropsychiatric condition with polysystemic disturbances, frequently co-occurring with irritable bowel syndrome (IBS). While traditionally viewed through psychological frameworks, emerging evidence suggests measurable biological alterations may underlie these conditions. This systematic review examined diagnostic biomarker profiles in SAD patients with IBS. Following PRISMA guidelines, we included 18 studies comprising 2,504 participants with somatoform disorders and 335 controls. Consistent findings included elevated morning serum cortisol (10 of 12 studies), flattened cortisol awakening response (4 of 5 studies). These findings suggest hypothalamic-pituitary-adrenal axis dysregulation and sympathetic activation in SAD patients. While biomarkers showed moderate diagnostic utility (sensitivity 62-78%, specificity 71-85%), they support a biopsychosocial rather than purely psychological conceptualization. Emerging evidence suggests some individuals with SAD exhibit measurable neuroendocrine dysfunction, though mechanisms remain distinct from organic conditions and whether alterations represent predisposing factors or consequences remains unclear.